2021
DOI: 10.1097/mpg.0000000000003216
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Predictors and Outcomes for Recurrent Pneumatosis Intestinalis in Children: A Case Control Study

Abstract: Introduction: Pneumatosis intestinalis (PI) is air collections within the wall of the intestine that can be associated with life threatening conditions. Recurrent episodes of PI have been reported; however, little is known about risks for recurrent disease. This study aims to identify predictors of recurrent PI and evaluate long-term outcomes in patients with recurrent PI. Methods: This retrospective case-control study evaluated patients, ages 6 months to 18 years, with imaging evidence of PI over a 30-month p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Prior studies focusing on recurrent PI have identiied an anatomical association in that PI located in the small bowel is more likely to recur than PI located in the large bowel, however, the reasons for this is unclear (15). An interesting inding of this study was the association between type of nutritional support and the development of PI.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Prior studies focusing on recurrent PI have identiied an anatomical association in that PI located in the small bowel is more likely to recur than PI located in the large bowel, however, the reasons for this is unclear (15). An interesting inding of this study was the association between type of nutritional support and the development of PI.…”
Section: Discussionmentioning
confidence: 80%
“…However, this series is too small to offer to support to this theory and more data are needed. Prior studies focusing on recurrent PI have identified an anatomical association in that PI located in the small bowel is more likely to recur than PI located in the large bowel, however, the reasons for this is unclear (15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations